279 Quality Improvement Audit on Bone Health Assessment and Secondary Prevention of Patients Discharged from an In-patient Rehabilitation Unit Post Fracture. (16th September 2019) - Synnott, Pádraig; Brennan, Michelle; O'Keeffe, Shaun; Canavan, Michelle
Abstract: Background: Osteoporosis accounts for more disability-adjusted life years than many non-communicable diseases. Identification and treatment is important to reduce morbidity and mortality associated with further fracture.(1) National Osteoporosis Guideline Group recommends all patients with a fragility fracture should undergo a bone health assessment and commence pharmacological therapy if indicated.(2) Methods: Electronic discharge summaries of all patients with a diagnosis of fracture discharged from an off-site rehabilitation unit from 1 st January 2018 to 31 st December 2018 were reviewed. Patient details, location and mechanism of fracture, bone health assessment and discharge prescription were assessed. Following data collection, an education session directed at NCHDs was performed and a discharge checklist prompting bone health review and consideration of pharmacological therapy was introduced. A re-audit was performed at 4 months to assess change following this intervention. Results: 74 patients had a diagnosis of fracture. 4 were excluded as fracture resulted from high impact trauma. 100% had corrected calcium measured. 93%(n=65) had Vitamin D(OH) measured. 91%(n=64) had PTH measured. 55%(n=39) were discharged on calcium/vitamin D(OH) supplementation. 33%(n=23) were discharged on Vitamin D(OH) alone. 66%(n=46) were discharged on antiresorptive therapy: 28%(n=13) bisphosphonate, 67% (n=31) denosumab, 4% others. 33%(n=23) were not prescribed any bone protection on discharge. 4 had advanced chronic kidney disease. 6%(n=4) were discharged without calcium/Vitamin D or antiresorptive therapy. A re-audit from January to April 2019 of 15 patients post NCHD education has shown an increase in antiresorptive therapy prescription 86%(n=13) Conclusion: Bone health assessment and prescribing practices of antiresorptive therapy in patients undergoing rehabilitation post fracture is sub-optimal. Education of non-consultant hospital doctors can substantially improve rates of antiresorptive therapy prescription.